A novel, effective and low cost electrocatalyst for direct methanol fuel cells applications - Döner, Ali; Kardaş, Gülfeza (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Electrocatalytic oxidation of methanol in alkaline solution on a NiCd/C catalyst chemically modified by a leaching process of Zn was investigated. Scanning electron microscopy (SEM), X-ray florescence spectroscopy (XRF) and atomic force microscopy (AFM) were used for coating characterization. The electrochemical properties and behaviors and also kinetic values of alkaline leached NiCdZn/C catalyst were characterized using cyclic voltammetry (CV), chronoamperometry (CA) and electrochemical impedance spectroscopy (EIS). The electrocatalytic activity of the alkaline leached NiCdZn/C catalyst toward methanol oxidation is shown to strongly depend on the porous and larger structure of coating and increasing of electrocatalytic active sites. The prepared catalyst in the present work is the most promising system for use in direct methanol fuel cells.
Keywords: Fuel cells; Methanol oxidation; Non platinum; Modified electrode; Ternary catalayst